The effective strategist key skills for all managers - Van Maurik, John 1948- (Gower, 1999)
Putting strategic thinking within the reach of all managers, this book covers the breadth of business life - from effective marketing and innovation to handling organizational politics. It challenges managers to think strategically and apply that thinking with confidence.